2013
DOI: 10.1007/s00221-013-3598-x
|View full text |Cite
|
Sign up to set email alerts
|

Observation learning of a motor task: who and when?

Abstract: Observation contributes to motor learning. It was recently demonstrated that the observation of both a novice and an expert model (mixed observation) resulted in better learning of a complex spatiotemporal task than the observation of either a novice or an expert model. In experiment 1, we aimed to determine whether mixed observation better promotes learning due to the information that can be gained from two models who exhibit different skill levels or simply because multiple models, regardless of their level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 43 publications
8
27
0
Order By: Relevance
“…We suggest that participants’ observational learning in the present study was likely bolstered by watching a live model (their partner) transition from novice to expert status as a knot tyer, as prior research suggests observing both experts and novices at a given motor task leads to improved observational learning of that same task [71, 72]. Future investigations into how observational experience shapes object representations could vary how much information participants know about the task and later performance expectations, as evidence suggests that more information about the task or future performance evaluation benefits observational learning [73, 74].…”
Section: Discussionmentioning
confidence: 78%
“…We suggest that participants’ observational learning in the present study was likely bolstered by watching a live model (their partner) transition from novice to expert status as a knot tyer, as prior research suggests observing both experts and novices at a given motor task leads to improved observational learning of that same task [71, 72]. Future investigations into how observational experience shapes object representations could vary how much information participants know about the task and later performance expectations, as evidence suggests that more information about the task or future performance evaluation benefits observational learning [73, 74].…”
Section: Discussionmentioning
confidence: 78%
“…In healthy participants, seeing others perform a motor task leads to motor facilitation (Ménoret et al, 2013) and motor learning (McCullagh et al, 1989; Hodges et al, 2007; Wulf and Mornell, 2008) on the part of the observer. In particular, observers appear to benefit from observing both experts and novices perform a motor task, thus learning from errors as well as exemplary performance (Andrieux and Proteau, 2013). As a result, action observation has been proposed recently as a tool for motor-rehabilitation after stroke (Garrison et al, 2010, 2013; Sale and Franceschini, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that observation of a novice and an expert model produced better retention than observation of either two novice or two expert models [66]. Furthermore, observational learning followed by or interspersed with physical practice of the task, as compared to observational learning alone, leads to superior learning [66], [72], and importantly, physical practice provides an advantage over observational learning alone [73].…”
Section: Observational Learningmentioning
confidence: 93%
“…The display usually consists of computerized visual and/or auditory presentations. There is a growing body of literature in support of observational learning, showing that movement strategies (e.g., [61]), discrete spatial information (e.g., [62], [63]), spatial sequences (e.g., [64], [65]), timing (e.g., [66]), and even dynamic movements such as dance [67] and surgery [68] can benefit from observational learning. A common form of observational learning is by visual demonstration of a skill.…”
Section: Observational Learningmentioning
confidence: 99%